A new species of the genus Amyrsidea (Phthiraptera: Amblycera: Menoponidae) parasitizing domestic chickens in Saudi Arabia - Alahmed, Azzam; Aldryhim, Yousif; Shobrak, Mohammed; Nasser, Mohamed (Zootaxa, 2017)
Amyrsidea Ewing, 1927 is a genus of chewing lice comprising 52 species, divided into five subgenera: Amyrsidea sensu stricto, Argimenopon Eichler, 1947, Cracimenopon Carriker, 1954, Desumenopon Carriker, 1954 and Numidimenopon Scharf & Price, 1977 (see Price et al. 2003: 86), which parasitise a wide range of hosts belonging to the avian order Galliformes (see Price et al. 2003: 321). Species of Amyrsidea can be distinguished from species of Menacanthus Neumann, 1912—the other menoponid genus with species parasitic on the same hosts—by lacking ventral spinous processes in the head (Scharf & Price 1977: 815). Revisions of all subgenera and species of Amyrsidea, including keys for their identification, were published by Scharf & Price (1977, 1983) and Scharf & Emerson (1983, 1984).